Implementation of 2d strongly autonomous behaviors by full and partial interconnections - Diego Napp Avelli (2009)
In this paper we study linear discrete two-dimensional systems in the behavioral context where control is viewed as interconnection. Within the behavioral framework a natural concept of interconnection has been introduced by J.C.Willems, called regular interconnection. We investigate regular interconnections that yield finite dimensional behaviors, and prove that when a finite dimensional behavior can be achieved from a given behavior B by regular full/partial interconnection then the controllable part/manifest part of B is rectifiable.